Attachment and Emotional Regulation in a Semi-Military Academy: a Case Study of Homesickness and Student Adaptation - Zunaina Zamhariri; Sierra Sinta Sunarso Putri; Aqila Nadra Rabbani (International Conference on Psychology and Education (ICPE), 2025)
This study presents a case of a first-year female student at Politeknik Pelayaran Surabaya who experienced intense homesickness during her transition to a semi-military academy. Drawing from direct observation, alloanamnesis, and autoanamnesis interviews, the findings reveal how her strong emotional attachment to her family, especially her mother, created persistent emotional instability that affected her academic focus, motivation, and social interactions. While she possessed adequate cognitive abilities and discipline, her emotional state often led to procrastination, withdrawal, and fluctuations in concentration. However, the student gradually developed adaptive strategies, such as peer support, marching band participation, watching videos, and structured communication with family, which strengthened her emotional regulation. The novelty of this research lies in documenting the interplay of attachment and emotional regulation within the unique context of an Indonesian semi-military academy—a field rarely explored in existing literature. Beyond theoretical contribution, the practical implications highlight the need for structured emotional regulation training, psychoeducation for parents, and peer mentoring programs to support first-year students in overcoming separation distress. By emphasizing both the challenges and adaptive processes, this study provides insights for institutions to design interventions that balance family attachment with autonomy development.